ANALISIS PERAN KOMITE SEKOLAH DALAM PERENCANAAN PENGEMBANGAN SEKOLAH DASAR NEGERI 71 KOTA BANDA ACEH - Haryanti, Tiara; Hambali, Hambali; Maulidar, Maulidar (Jurnal Dedikasi Pendidikan, 2025)
This research is based on problems that have been encountered at SDN 71 Banda Aceh which is directly related to the school committee in several ways which supports. This can be seen from the results of observations that the school committee no input into the learning process, no mobilization managing resources and not monitoring the participation of educational stakeholders in implementing school programs. This study aims to determine what is the role of the school committee in planning the development of SD Negeri 71 Banda Aceh City. This research uses a qualitative approach using descriptive methods with data collection techniques carried out by conducting observations and interviews. The subjects in this research are 1 chairman of the school committee, 1 principal, 2 teachers, and 2 people  parents/guardians of students. The data processing technique in this research uses data collection, data reduction, data presentation, and verification using the descriptive analysis formula. The research results from observation data are that Facilitation supports the role of school committees in development planning SD Negeri 71 has 43 items with a percentage of 91.5% in the very good category, Facilitation that does not support there are 4 items with a percentage of 8.5% in the category very less. So, in general from the results of the interview analysis research that The school committee has supporting factors such as the similarity of vision schools and school committees that make good cooperation and factors barriers such as a lack of consideration and internal control implementation of the program and learning process